2014
DOI: 10.1515/cclm-2014-0505
|View full text |Cite
|
Sign up to set email alerts
|

The serum uromodulin level is associated with kidney function

Abstract: Serum uromodulin behaves in a manner opposite that of the different conventional renal retention markers by displaying lower concentrations with decreasing kidney function. As uromodulin is produced by the cells of the thick ascending limb of the loop of Henle, lower uromodulin serum levels may reflect a reduction in number or function of these cells in chronic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
53
1
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 14 publications
12
53
1
5
Order By: Relevance
“…This suggests that even serum Uromodulin levels correlated positively with low eGFR where Uromodulin secreting cells were almost destroyed. Recently, Risch et al [15] have also documented significant differences (p<0.001) in serum Uromodulin among the four groups according to different kidney function stages Further in their study, serum Uromodulin displayed inverse relationships with creatinine (r=-0.39) and a positive relationship with eGFRCysC (r=0.38, p<0.001) similar to that found in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that even serum Uromodulin levels correlated positively with low eGFR where Uromodulin secreting cells were almost destroyed. Recently, Risch et al [15] have also documented significant differences (p<0.001) in serum Uromodulin among the four groups according to different kidney function stages Further in their study, serum Uromodulin displayed inverse relationships with creatinine (r=-0.39) and a positive relationship with eGFRCysC (r=0.38, p<0.001) similar to that found in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…We observed similar findings in the mouse, where THP can also be localized to the interstitial space and around the basolateral domain of proximal S3 segments (15). In fact, beyond the interstitium between TAL and S3, THP can also be detected in the serum (8,51,54,66). Seminal data from Thornley et al (66), recently validated by others (54), showed that both urinary and serum THP are proportionally correlated with level of kidney function.…”
Section: Tubular Cross Talk In Ischemia-reperfusionsupporting
confidence: 81%
“…In fact, beyond the interstitium between TAL and S3, THP can also be detected in the serum (8,51,54,66). Seminal data from Thornley et al (66), recently validated by others (54), showed that both urinary and serum THP are proportionally correlated with level of kidney function.…”
Section: Tubular Cross Talk In Ischemia-reperfusionmentioning
confidence: 99%
“…dIsCussION In the present study, we showed that serum uromodulin concentrations in patients with CKD were significantly lower than in healthy subjects, and that the lower concentrations were associated with more advanced stages The relationship between renal function and serum or plasma uromodulin concentrations has been less extensively studied than that between renal function and urinary uromodulin levels, and the results of these studies are inconsistent. 6,23,[28][29][30] In 1985, Thornley et al 30 showed increased plasma concentrations of uromodulin in 65 patients with CKD and observed a positive correlation between the measured clearance of endogenous creatinine and concentration of uromodulin in plasma; however, they did not observe such a correlation in 26 healthy subjects. More recently, Prajczer et al 29 studied uromodulin concentrations in serum and urine in 14 healthy persons and 77 patients with CKD.…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22] Most studies conducted so far have focused on uromodulin levels in urine, while the occurrence of uromodulin in blood and its serum concentrations have not been extensively studied with respect to CKD. 23 The aims of our study were to evaluate serum uromodulin concentrations in patients with stages 1 to 5 of CKD regardless of the cause of the disease, and to assess the relationship between serum uromodulin levels and kidney function, as reflected by the markers of renal retention (serum creatinine and cystatin C) as well as the estimated glomerular filtration rate (eGFR). Moreover, we assessed the diagnostic accuracy of the measurement of serum uromodulin levels to differentiate between healthy individuals and CKD patients and to diagnose CKD stages.…”
Section: Original Articlementioning
confidence: 99%